Perbandingan Sanksi Pidana dan Sanksi Administratif pada Pelanggaran Ringan Hukum Kesehatan di Berbagai Negara - Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2024)
Enforcement of public health laws requires effective sanctioning instruments to ensure compliance. In dealing with minor offences, there are differences in the use of criminal and administrative sanctions in various countries. This study compares the application of both types of sanctions in health law systems in several countries. The analysis shows that administrative sanctions are used more frequently than criminal sanctions to deal with minor health law violations. Administrative sanctions are considered more effective, efficient, and proportional due to their faster and more flexible enforcement process, as well as their more moderate penalties. On the other hand, criminal sanctions are more applicable for more serious offences that significantly threaten public health, as they provide a stronger deterrent effect. The right combination of criminal and administrative sanctions is key to achieving comprehensive and effective health law enforcement. The selection of the type of sanction in accordance with the seriousness of the offence as well as the cultural context and legal system of each country is an important factor in its application.